Defining genetic diversity of rhesus macaque Fcγ receptors with long-read RNA sequencing - Conley, Haleigh E.; He, Max M.; Easterhoff, David; Kirshner, Hélène Fradin; Cocklin, Sarah L.; Meyer, Jacob; Hoxie, Taylor; Berry, Madison; Bradley, Todd; Tolbert, William D.; Pazgier, Marzena; Tomaras, Georgia D.; et al. (Frontiers in Immunology, 2024)
Fc receptors (FcRs) are membrane-bound glycoproteins that bind to the fragment crystallizable (Fc) constant regions of IgG antibodies. Interactions between IgG immune complexes and FcRs can initiate signal transduction that mediates important components of the immune response including activation of immune cells for clearance of opsonized pathogens or infected host cells. In humans, many studies have identified associations between FcR gene polymorphisms and risk of infection, or progression of disease, suggesting a gene-level impact on FcR-dependent immune responses. Rhesus macaques are an important translational model for most human health interventions, yet little is known about the breadth of rhesus macaque FcR genetic diversity. This lack of knowledge prevents evaluation of the impact of FcR polymorphisms on outcomes of preclinical studies performed in rhesus macaques. In this study we used long-read RNA sequencing to define the genetic diversity of FcRs in 206 Indian-origin Rhesus macaques, Macaca mulatta. We describe the frequency of single nucleotide polymorphisms, insertions, deletions, frame-shift mutations, and isoforms. We also index the identified diversity using predicted and known rhesus macaque FcR and Fc-FcR structures. Future studies that define the functional significance of this This is a provisional file, not the final typeset article genetic diversity will facilitate a better understanding of the correlation between human and macaque FcR biology that is needed for effective translation of studies with antibody-mediated outcomes performed in rhesus macaques.